Penerapan Collaborative Learning dalam Pembelajaran White-Box Testing: Studi Kasus pada Pengujian Looping dan Condition Branch - Zulkipli, Zulkipli; Putri, Lara Aulia; Aranbi, Muhammad Defa; Purnomo, Reno; Wea, Yohanes Emanuel Dala (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Software testing learning, particularly white-box testing, is an important competency in Information Technology Education, but it remains a challenge for students because it requires an understanding of complex program logic. Difficulties arise mainly in the material on testing program control structures, such as looping and condition branches. This study aims to analyse the application of the collaborative learning method in white-box testing learning in this material. The research used a qualitative descriptive approach with a case study design involving students from the Information Technology Education Study Programme. Data were collected through observation of the learning process, analysis of group assignment results, and student reflections. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the application of collaborative learning can improve students' conceptual understanding, program logic analysis skills, and cooperation skills in solving source code testing problems. In addition, students showed increased activity in discussions and the ability to explain program logic flows systematically. Thus, the collaborative learning method is effective in white-box testing learning, especially in looping and condition branch material.